Aplikasi Project Based Learning (PjBL)di KB-RA Terapi Tazkiyah Malang - Herawati, Siane; Cholifah, Maria; Muzammil, Lasim; Andy, Andy (Jurnal Pengabdian Masyarakat (ABDIRA), 2024)
KB-RA Tazkiyah Therapy provides opportunities for children with special needs such as the blind, deaf, ADHD or ABK to get equal opportunities in the learning process. Taking into account the needs of children and the condition of the school as well as the facilities needed for normal students and those with special needs, as well as age differences, the service teaches Project based Learning (PjBL) for all students, both normal and those with special needs. This community service activity takes the form of fun cooking, namely decorating cupcakes for Tazkiyah KB-RA Therapy students. The application of this training is to increase feelings of empathy, cooperation among students who have different ages, the conditions of normal students and students with special needs who are in the same class as other students. The method applied in this activity is the training of decorating cupcakes. Some of the benefits that can be obtained from KB-RA and TAZKIYAH THERAPY through community service activities are: (1) Gaining creative knowledge and skills in decorating cup cakes (fun cooking) (2) Gaining knowledge in applying Project based Learning (PjBL).